2020 International Consensus on First Aid Science With Treatment Recommendations. (November 2020) - Singletary, Eunice M.; Zideman, David A.; Bendall, Jason C.; Berry, David A.; Borra, Vere; Carlson, Jestin N.; Cassan, Pascal; Chang, Wei- Tien; Charlton, Nathan P.; Djärv, Therese; Douma, Matthew J.; Epstein, Jonathan L.; et al.
Abstract: This is the summary publication of the International Liaison Committee on Resuscitation's 2020 International Consensus on First Aid Science With Treatment Recommendations . It addresses the most recent published evidence reviewed by the First Aid Task Force science experts. This summary addresses the topics of first aid methods of glucose administration for hypoglycemia; techniques for cooling of exertional hyperthermia and heatstroke; recognition of acute stroke; the use of supplementary oxygen in acute stroke; early or first aid use of aspirin for chest pain; control of life- threatening bleeding through the use of tourniquets, haemostatic dressings, direct pressure, or pressure devices; the use of a compression wrap for closed extremity joint injuries; and temporary storage of an avulsed tooth. Additional summaries of scoping reviews are presented for the use of a recovery position, recognition of a concussion, and 6 other first aid topics. The First Aid Task Force has assessed, discussed, and debated the certainty of evidence on the basis of Grading of Recommendations, Assessment, Development, and Evaluation criteria and present their consensus treatment recommendations with evidence-to-decision highlights and identified priority knowledge gaps for future research. The 2020 International Consensus on Cardiopulmonary Resuscitation (CPR) and Emergency Cardiovascular Care (ECC) Science With Treatment Recommendations (CoSTR) is the fourth in a series of annual summary publications from the International Liaison Committee on Resuscitation (ILCOR). This 2020 CoSTR for first aid includes new topics addressed by systematic reviews performed within the past 12 months. It also includes updates of the first aid treatment recommendations published from 2010 through 2019 that are based on additional evidence evaluations and updates. As a result, this 2020 CoSTR for first aid represents the most comprehensive update since 2010.